Perbedaan Angka Kuman Udara Ruang Operasi Sebelum dan Sesudah Sterilisasi Ultraviolet - Luky Rinda Meiriana; Imam Santoso; Erminawati Erminawati (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2018)
Difference In The Number Of Airborne Operation Room Before And After UV Sterilization. Hospitals become one where the occurrence of environmental pollution, health problems or can be a place of disease transmission. The operating room is a potentially high room causing nosocomial infections in the hospital, especially surgical wound infections. Bacteriological qualities of the general surgery and in-room surgery room, the researchers assume that there are variations in different ratio rates on the stages of laboratories measurement results. So it takes empirical clarity to see the difference. This study aimed to determine the difference in the number of airborne operating room fluid before and after UV sterilization in RSUD Ratu Zalecha Martapura. This study used design of experiments (one group pre and post test design), Population in this research was amount of air of operating room at Ratu Zalecha Martapura Hospital. The sample of this research was the air space bacteria OK 1 Ratu Zalecha Martapura Hospital total operating room amounted to 5 rooms.. Data were analyzed used paired sample t-test. The results of this study indicate that there are significant differences before surgery after sterilization with postoperative 1 before sterilization p value (0.015) ≤ nilai  (0.05). Advice for sterilization officers operating room are check UV rays effectivity, maintenance of UV lighting and sterilization process should be done after room sterilization.